Common asset trusts to effectively steward natural capital and ecosystem services at multiple scales. (15th February 2021) - Costanza, Robert; Atkins, Paul W.B.; Hernandez-Blanco, Marcello; Kubiszewski, Ida
Abstract: Ecosystems (natural capital) produce a range of benefits to humans. Natural capital is best thought of as common property since many of the ecosystem services it helps produce are non-rival and/or non-excludable. Private property regimes and markets alone are ineffective and inappropriate institutions to manage them sustainably. These systems can be better managed as commons, using more nuanced private and community property rights and Common Asset Trusts (CATs), with legal precedent in the Public Trust Doctrine. Effective CATs embody a generalized version of Elinore Ostrom's eight core design principles for sustainable commons management: (1) shared identity and purpose; (2) equitable distribution of contributions and benefits; (3) fair and inclusive decision-making; (4) monitoring agreed behaviours; (5) graduated responses; (6) fast and fair conflict resolution; (7) authority to self-govern; and (8) collaborative relations with other groups and spatial scales. Here, we describe a few existing and proposed systems that approximate effective CATs. We also suggest how Costa Rica can transform its existing payment for ecosystem services (PES) scheme into a national CAT. Finally, we describe how CATs can facilitate more fair and effective public/private partnerships (PPPs) to invest in natural capital and ecosystem services. Highlights: Integrated private and common property regimes are needed to manage natural capital (NC). Common Asset Trusts (CATs) are effective institutions for integrated NC stewardship. Effective CATs are based on Ostrom's 8 core design principle for commons management. We describe existing CATs and propose a national CAT for Costa Rica. CATs can facilitate public/private partnerships (PPPs) to invest in natural capital.